Diabetes control is worse in children and young people with type 1 diabetes requiring interpreter support - Idkowiak, Jan; Uday, Suma; Elhag, Sabba; Barrett, Timothy; Dias, Renuka; Kershaw, Melanie; Mohamed, Zainaba; Saraff, Vrinda; Krone, Ruth E. (Frontiers in Clinical Diabetes and Healthcare, 2023)
Introduction: Language barriers can pose a significant hurdle to successfully educating children and young people with type 1 diabetes (CYPD) and their families, potentially influencing their glycaemic control. Methods: Retrospective case-control study assessing HbA1c values at 0, 3, 6, 9, 12 and 18 months post-diagnosis in 41 CYPD requiring interpreter support (INT) and 100 age-, sex-and mode-of-therapy-matched CYPD not requiring interpreter support (CTR) in our multi-diverse tertiary diabetes centre. Data were captured between 2009-2016. English indices of deprivation for each cohort are reported based on the UK 2015 census data.The main languages spoken were Somali (27%), Urdu (19.5%), Romanian (17%) and Arabic (12%), but also Polish, Hindi, Tigrinya, Portuguese, Bengali and sign language. Overall deprivation was worse in the INT group according to the Index of Multiple Deprivation (IMD [median]: INT 1.642; CTR 3.741; p=0.001). The median HbA1c was higher at diagnosis in the CTR group (9.95% [85.2 mmol/mol] versus 9.0% [74.9 mmol/mol], p=0.046) but was higher in the INT group subsequently: the median HbA1c at 18 months post diagnosis was 8.3% (67.2 mmol/mol; INT) versus 7.9% (62.8 mmol/mol; CTR) (p=0.014). There was no hospitalisation secondary to diabetes-related complications in either cohorts. Glycaemic control is worse in CYPD with language barriers. Health care providers should offer tailored support for CYP/families with language barriers, and explore additional factors contributing to poor glycaemic control. The findings of this study suggest that poor health outcomes in CYPD with language barriers is multifactorial and warrants a multi-dimensional management approach.